Effects of Some Forage Crops and Mixture on Sunflower Yield and Soil Nitrogen Content - B. HAKYEMEZ, HAKAN; KAVDIR, YASEMIN (Asian Journal of Chemistry, 2010)
This research was conducted in Dardanos Research Center in Canakkale during 2003-2005 growing seasons. The aim of this research was to investigate effects of forage crops (common vetch, common vetch + barley, narbonne vetch) on soil nitrogen contents and sunflower yield. Two years results showed that leguminous and common vetch + barley mixture had greater biomass and higher N concentration and therefore, it increased sunflower seed yield. When forage crops were removed from the field for hay, it still supplied N for the sunflower. Sunflower seed yield increased 10.57 to 16.09 % after mixing as green manure and harvesting as hay, respectively compared to control.